A study on the performance of local exhaust ventilation system using Mahalanobis approach - Muhammad Hasbi, Abd Halid (2013)
The title of this experiment is a study on the performance of local exhaust ventilation system using Mahalanobis approach. The objectives of this study are to obtain normal pattern operation of local exhaust ventilation (LEV) system and to characterize the pattern to study the performance of the above system. An experiment was conducted in determining the average face velocity of the fume hood. This was done by taking several readings at equidistant points. The average face velocity was checked on reference guidelines of fume hood to see whether the fume hood is safe to use or otherwise. Then, with the same data obtained from the experiment, it was analysed using Mahalanobis Distance approach. Then, the result of both methods will be compared. After it had been analysed, 5 points of face velocity were obtained compared to the 16 initial points, thus proving Mahalanobis approach making it a better and faster way in determining the performance of the fume hood and the LEV system.